Physicochemical, textural and organoleptic properties of reduced fat cheddar chees - Nateghi, Leila (2011)
Dairy products, particularly cheese products are the main source of saturated fats and cholesterol. It is well established that excessive consumption of fat increases the risk of ailments like obesity and cardiovascular diseases. Reduced and low fat cheese often exhibit poor sensory quality due to the reduction of fat which plays a critical role in flavor and texture. The major objective of this research is to improve the textural and the organoleptic properties of the reduced fat cheddar cheese by the application of special adjunct starter cultures (Lactobacillus helveticus, Lactobacillus casei, Streptococcus thermophilus) and fat replacers namely xanthan gum and sodium caseinate. Initially different xanthan gum to sodium caseinate ratios (xanthan gum: 0, 0.015, 0.030,0.045 (% w/w), Sodium caseinate: 0, 0.15, 0.30, 0.45 (% w/w)) were added as fat replacer to different fat levels of cheese milk (1.25, 2, 2.75, 3.5) (% w/w) in order to investigate their ability to improve textural properties and yield of reduced fat cheddar cheese. Textural optimization was applied to obtain the best formulation to produce reduce fat cheddar cheese by using fat replacers. The results revealed that the type and concentration of fat replacers significantly (p < 0.05) affected the textural and composition of reduced fat cheddar cheeses. The multiple optimization results of the current study showed that using the high level of xanthan gum (0.045% w/w) in absence of sodium caseinate (0.000% w/w) in half-fat cheeses (2.000% w/w milk fat content) improved the texture and yield of cheddar cheeses with similar textural properties (TPA) of full fat ones and overall desirability of 90.065%. The best optimum formulation was chosen in order to develop the flavor by using single and mixed adjunct starter cultures (i.e. Lactobacillus helveticus, Lactobacillus casei,Streptococcus thermophilus). Profiles of organic acid concentrations, free amino acids, volatile flavor compounds and consumer acceptability showed that the use of Lactobacillus helveticus (108) as an adjunct starter culture significantly (p < 0.05) improved the flavor score of reduced fat cheddar cheeses compared to use of Lactobacillus casei and Streptococcus thermophilus and full fat cheddar cheese as a control. Moreover,proteolytic rate of cheeses containing the adjunct starter culture were significantly greater than full fat cheddar cheese. The results obtained by the instruments in this study interestingly verified the descriptive sensory analysis results. Incorporation of xanthan gum with Lactobacillus helveticus allowed a considerable fat reduction with no detrimental effect on cheddar cheese overall quality and consumer acceptability. Although xanthan gum significantly affected the textural properties of reduced fat cheddar cheeses, the effect of sodium caseinate as a protein-based fat mimetic was imperceptible. Therefore, further extensive investigations are needed to clarify the effect of other fat mimetics and starter cultures on textural properties and flavor of reduced fat cheddar cheeses. This study recommends that a high quality reduced fat cheddar cheese can be obtained by using xanthan gum as carbohydrate-based fat mimetics and Lactobacillus helveticus as an adjunct starter culture.